Solution-processed pseudo-vertical organic transistors based on TIPS-pentacene. (September 2021) - Kneppe, D.; Talnack, F.; Boroujeni, B.K.; Teixeira da Rocha, C.; Höppner, M.; Tahn, A.; Mannsfeld, S.C.B.; Ellinger, F.; Leo, K.; Kleemann, H.
Abstract: Powerful and versatile transistors are indispensable to realize the vision of future flexible electronics, e.g., for wearable active-matrix displays, smart sensors, or radio-frequency identification tags. Organic thin-film transistors are considered to be a perfect match for flexible electronics. However, conventional organic thin-film transistors still do not match the demanding performance targets of many applications. Furthermore, often complex and expensive fabrication steps are employed for the fabrication of hero-devices, which is not compatible with the paradigm of low-cost production of flexible electronics. In this contribution, we present the first solution-processed vertical organic field-effect transistor (VOFET) with good on-state performance comparable to vacuum-processed VOFETs. This approach unites the advantages of a low-temperature, low-cost solution processing with an ultra-short channel transistor concept possibly enabling large-area, low-cost flexible electronics. We examine the influence of different crystal morphologies (spherulitic and ribbons) on the transistor performance by using spin- and shear-coating as solution-based deposition methods. The solution-processed VOFETs reach channel width-normalized transconductances of up to 0.26 μS/μm with a charge carrier mobility of 4.8 cm 2 /V. S-parameter measurements finally verify that transition frequencies up to 6 MHz are reachable with shear-coated TIPS-pentacene. However, compared to small molecule-based VOFETs, the solution-processed VOFETs show an unfavorably high off-state current and hysteresis, which are explained by background doping and charge carrier trapping. Hence, in order to advance with, further optimization of the semiconductor material and the insulator–semiconductor interface is thus required to qualify solution-processed VOFETs for commercial applications. Graphical abstract: Image 1 Highlights: We present the first solution-processed vertical organic field-effect transistor (VOFET). Examine the influence of different crystal morphologies (spherulitic and ribbons) on the transistor performance. Solution-processed VOFETs reach channel width-normalized transconductances of up to 0.26 μS/μm (µ = 4.8 cm²/Vs). S-parameter measurements finally verify that transition frequencies up to 6 MHz are reachable.